Analisis Rasio Efektivitas Dan Rasio Efisiensi Keuangan Untuk Mengukur Kinerja Keuangan Pemerintah Daerah Kota Pematang Siantar - Dika Firza Hadinata; Fitri Mentari Sitompul; Friska Enjelina Nainggolan; Nelly Nurvita Tambunan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
By doing this research aims to examine the financial performance of the Pematang Siantar City Government. This analysis uses Effectiveness ratio and efficiency ratio to assess financial performance. This study is included in the category of quantitative descriptive research. The data used comes from the Financial Report of the Pematang Siantar City Government for the 2020-2023 budget period. Financial ratio analysis is the method used to perform this analysis. The results of the research show that the financial performance of the Pematangsiantar City Government the effectiveness ratio level of PAD receipts in Pematang Siantar City is very effective and for the level of efficiency ratio is still above 90% indicating that financial performance is less efficient Regional.